Cross‐sectional area reference values for peripheral nerve ultrasound in adults: A systematic review and meta‐analysis—Part II: Lower extremity nerves. (7th May 2021) - Fisse, Anna Lena; Katsanos, Aristeidis H.; Gold, Ralf; Krogias, Christos; Pitarokoili, Kalliopi
Abstract: Background and purpose: Measurement of the cross‐sectional area (CSA) of peripheral nerves using ultrasound is useful in the evaluation of focal lesions such as entrapment syndromes and inflammatory polyneuropathies. We performed a systematic review and meta‐analysis of published CSA reference values for lower extremity nerves. Methods: We included available‐to‐date nerve ultrasound studies on healthy adults and provide meta‐analysis for CSA of the following nerves: fibular nerve at fibular head, popliteal fossa; tibial nerve at popliteal fossa, malleolus; and sural nerve at the level of the two heads of gastrocnemius muscle. We report regression and correlation analyses for age, gender distribution, height, weight, and geographic continent. Results: We included 16 studies with 1001 healthy volunteers (mean age = 47.9 years) and 4023 examined nerve sites. Calculated mean pooled CSA of fibular nerve at fibular head was 8.4 mm 2 (95% confidence interval [CI] = 6.8–9.9 mm 2, n  = 1166), at popliteal fossa was 7.9 mm 2 (95% CI = 6.6–9.2 mm 2, n  = 995), of tibial nerve at popliteal fossa was 25.9 mm 2 (95% CI = 17.5–34.4 mm 2, n  = 771), at malleolus was 10.0 mm 2 (95% CI = 7.7–12.4 mm 2, n  = 779), and of sural nerve was 2.4 mm 2 (95% CI = 1.7–3.1 mm 2, n  = 312). Substantial heterogeneity across studies ( I 2  > 50%) was found only for tibial nerve at popliteal fossa. Subgroup analysis revealed a lower CSA of tibial nerve at popliteal fossa and sural nerve in studies conducted in Europe than in North America and New Zealand. Conclusions: We provide the first meta‐analysis on CSA reference values for the lower extremities with no or low heterogeneity of reported CSA values in all nerve sites except tibial nerve at popliteal fossa. Our data facilitate the goal of an international standardized evaluation protocol.